Comparing Two Measures of Electoral Integrity in the American States. (March 2019) - Flavin, Patrick; Shufeldt, Gregory
Abstract : We compare two widely publicized measures of state electoral integrity in the United States: the Electoral Integrity Project's 2016 U.S. Perceptions of Electoral Integrity Survey and the Pew 2014 Elections Performance Index. First, we review the theoretical and empirical differences between the two measures and find that they correlate at a surprisingly low level across the states. Second, given this low correlation, we examine the component parts of these indices and find that both are capturing multiple dimensions. Third, we examine how the components and the individual indicators that comprise each measure are linked to citizens' stated perceptions about electoral integrity. Throughout the article, we articulate a set of preemptive recommendations that urge researchers to be cautious and deliberate when choosing among measures of electoral integrity to use in future empirical studies.